Pengaruh Muatan Berlebih (Overloading) Kendaraan Berat terhadap Umur Rencana Jalan pada Ruas Jalan Kopang – Masbagik - Humaerok, Siti Nilza; Efendy, Anwar; Hidayati, Nurul (Universitas Batanghari Jambi, 2026)
Roads are basic infrastructure facilities needed by humans to move from one location to another in order to fulfill their needs. Essentially, the structural quality of roads will deteriorate as the road ages, especially if they are used by vehicles with heavy loads that tend to exceed the regulations. The Kopang–Masbagik road section in West Nusa Tenggara Province is a national road with heavy traffic and a predominance of heavy vehicles. This condition causes an increase in traffic load, mainly due to overloading, which can accelerate pavement damage and reduce the planned road life. This study aims to analyze the effect of heavy vehicle overloading on the planned road life using the 2024 Bina Marga method with the Cumulative Equivalent Single Axle Load (CESAL) approach. The data used includes Average Daily Traffic (ADT) from BPJN West Nusa Tenggara and vehicle weighing data from UPPKB Bertais. The analysis results show that under normal conditions, the cumulative CESAL value over a 10-year design life is 84,338,823 ESA, with the final Remaining Life (RL) reaching 0%, consistent with the design life. However, under overload conditions, the cumulative CESAL value increases dramatically to 250.658.619 ESA. The impact of overloading causes a reduction in the planned lifespan; based on calculations carried out, there is a decrease in the planned lifespan of 0.552 years from the planned lifespan of 10 years.